Multiple Outbursts of Halley-type Comet 12P/Pons–Brooks - David Jewitt; Jane Luu (The Astronomical Journal)
We present optical observations of the Halley-type comet 12P/Pons–Brooks (12P) on its approach to perihelion. The comet was active even in the first observations at ∼8 au. Starting at ∼4 au, 12P exhibited an extraordinary series of outbursts, in which the brightness changed by a factor up to 100 and the coma morphology transformed under the action of radiation pressure into a distinctive “horned” appearance. Individual outburst dust masses are several ×10 ^9 kg, with kinetic energies ∼10 ^14 J, release times ∼10 ^4 s, and effective power ∼10 ^10 W. These properties are most consistent with, although do not definitively establish, an origin by the crystallization of amorphous water ice with the related release of trapped supervolatile gases. This interpretation is supported by the observation that the specific outburst energy and the specific crystallization energy are comparable (both ∼10 ^5 J kg ^−1 ).